PROTOCOL: Interview and interrogation methods and their effects on true and false confessions: An update and extension. Issue 1 (2nd March 2023) - Catlin, Mary; Wilson, David B.; Redlich, Allison D.; Bettens, Talley; Meissner, Christian A.; Bhatt, Sujeeta; Brandon, Susan
Abstract: This is the protocol for a Campbell systematic review. The objective is to assess the effects of interrogation approach on confession outcomes for criminal (mock) suspects.